Does playing video games effect cognitive abilities in Pakistani children? - Hisam, Aliya (Pak J Med Sci, 2018)
OBJECTIVE: To find out the effect of playing video games on cognitive abilities among teenagers. METHODS: A comparative cross sectional study was conducted at two schools in Rawalpindi from August 2014 till February 2015. A sample size of 171 was calculated by using WHO sample size calculator using non-probability convenient sampling technique. A mixed questionnaire was used as a data collection tool and two groups were defined as video gamers and non-video gamers. Video gamers were those students who were using video games for two hours or more. Cognitive ability of the students were assess by standardized questionnaire named Wonderlic Cognitive Ability Test Questionnaire. Data were entered and analyzed in SPSS version 20. RESULTS: There were 93 (54.4%) gamers whereas 78(45.4%) were non-gamers. Mean age of the participants was 18.86+1.46 years. Gamers with correct answers to knowledge, analogy, processing speed, deductive reasoning, mathematical intelligence were 57(61.3%), 67(72%), 68 (73%), 58 (62.4%) and 73(78.5%) respectively. Significant association was found between gamer status and gender (p=0.023), analogy (p=0.049), processing speed (p<0.001), deductive reasoning (p=0.003) and mathematical intelligence (p<0.001). There was no significant association of gamer status with knowledge (p=0.188). CONCLUSION: Gamers exhibit better range of cognitive abilities specifically involving analogy, processing speed, deductive reasoning and mathematical intelligence. In this study, those who play video games on long term basis, showed improvement in cognitive abilities, in comparison to those who do not indulge in gaming activities.